Natural and human impact on land use change of the Sikkimese-Bhutanese Himalayan Piedmont, India - Prokop, Paweł; Sarkar, Subir (Quaestiones Geographicae, 2012)
Natural and human causes of land use transformation were analysed in the Sikkimese-Bhutanese Himalayan piedmont over last 150 years with special emphasize on period 1930-2010. A hydrologic and geomorphic approach was employed to delineate three study areas along river courses on alluvial fans stretching 10 km from the mountain front. The visual interpretation of topographic maps and satellite images combined with logical rules in GIS were used for determination of stable and dynamic areas from the viewpoint of land use changes. Analysis indicates rapid replacement of natural forest through location of tea plantations, crop cultivation and development of settlement in the late 19th century. The shift from natural to human dominated landscape caused increase land use stability through enlargement of areas with monoculture cultivation of tea and paddy between 1930 and 2010. The natural fluvial activity intensified by human induced deforestation of Himalayan margin and clearance of riparian vegetation along foothill channels became the most important factors of present-day land use changes of piedmont.